Longitudinal Investigation of Psychotherapy Outcomes (LIPO): Description of the Study Protocol - Gonçalves, Leonardo; Barbisan, Guillherme Kirsten; Rebouças, Cinthia Danielle Araújo Vasconcelos; da Rocha, Neusa Sica (Frontiers in Psychiatry, 2019)
Background: Despite extensive research in the field of psychotherapies, few studies have compared the primary psychotherapies of naturalistic design, which represents real-life situations. Objective: The objectives of this study were to evaluate three modalities of evidence-based psychotherapy for clinical, psychosocial, and biological outcomes and to identify the mediators and confounders of this process. Our primary hypothesis is that all psychotherapies will improve clinical and psychosocial outcomes and will increase BDNF levels. Methods:Design: longitudinal, naturalistic. Participants: One hundred twenty-six patients who underwent one of three evidence-based modalities of individual psychotherapy [psychodynamic psychotherapy (PDT), interpersonal psychotherapy (IPT), and cognitive–behavioral psychotherapy (CBT)] were included. Measure: Primary outcomes are divided into three domains of variables: clinical (general psychiatric symptoms), biological (serum BDNF levels), and psychosocial (resilience, quality of life, coping strategies, social support, and quality of life-adjusted years of life). Confounding/mediator variables included clinical (personality traits, type of psychotherapy, number of sessions, concomitant use of pharmacological treatment, history of previous psychotherapeutic treatment, medical and psychiatric comorbidities, and psychiatric diagnosis), psychosocial (psychosocial stressors, therapeutic alliance, and defense mechanism style), and other (religiosity) factors. Procedure: The follow-up period will be baseline and 6 months and 1 year after entering the study. The study will include 42 controls for biological variables only. Sample size calculation considered a significance level of 5% and a power of 80% to detect a difference of 0.22 with a standard deviation of 0.43, assuming losses of 20–30% of patients. The comparison between the modalities of psychotherapy will be by generalized estimating equations (GEE) model, the analysis of mediators by the Hayes method, and confounders by multivariate logistic regression. Discussion: The findings of this study are intended to demonstrate the outcomes of evidence-based psychotherapies for clinical, psychosocial, and biological parameters and to understand the mediators and confounders of this process in a real-life setting for patients with severe mental illness, thus contributing to the establishment of evidence-based public health policies in the field of psychological interventions.